Histopathological study of heart and cardiac vessels in autopsy cases from tertiary health-care center - Kavitha Muniraj; Vincy TM; Boopathy, Teleflo; Prakasam, Gowri; Gowsalya Kannan (Asian Journal of Medical Sciences, 2024)
Background: Atherosclerosis is a chronic inflammatory disease causing more morbidity and mortality in developed as well as in developing countries. Among Indians, atherosclerotic lesions occur 10–15 years earlier, and the lesions are formed in the advanced stage. It is difficult and expensive to evaluate the atherosclerotic lesions in living subjects. Atherosclerosis of cardiac vessels and myocardial infarction are the most common fatal cardiac diseases discovered in autopsies. The incidence of coronary artery diseases is increasing worldwide as well as in India, which carries a huge challenge in diagnosing the same. Aims and Objectives: The aims and objectives are to study the spectrum of histopathological findings in heart and atherosclerotic lesions in cardiac vessels in autopsy cases. Materials and Methods: This is a retrospective study done in the Department of Pathology at Government Kilpauk Medical College and Hospital over a period of 1 year (March 2022–December 2022). In this study, a total of 100 autopsy cases were taken to study the pathology of the heart and the grading of atherosclerotic lesions in cardiac vessels. Heart specimens were received from the Forensic Medicine Department. The atherosclerotic lesions of cardiac vessels were graded according to the American Heart Association (AHA) classification. Results: Among 100 cases studied during a period of 1 year, most of the cases were in the age group of 30–41 years. Male preponderance was noted when compared to females. Out of 100 cases, 79 cases had histopathological evidence of atherosclerosis, and other findings were as follows: one case of giant cell myocarditis, one case of pericarditis, and one case of adenocarcinoma of the lung extending into the coronary vessels. The most common type of atherosclerotic lesion seen was type 7 AHA, most frequently involving the aorta, followed by both coronary ostia and the left anterior descending artery. Conclusion: In this study, atherosclerotic lesions were observed very frequently in younger individuals. It is an indication for the implementation of antiatherogenic preventive measures in young populations. It highlights the importance of screening for cardiovascular risk factors at an early age.